2016
DOI: 10.1159/000444258
|View full text |Cite
|
Sign up to set email alerts
|

Is Modified Radical Hysterectomy Needed for Patients with Clinical Stage I/II Endometrial Cancers? A Historical Control Study

Abstract: Objective: The aim of the present study was to assess whether hysterectomy with wider resection could improve survival by preventing local recurrence. Methods: Medical charts of the patients with clinical stage I/II endometrial cancers treated at our hospital between 1990 and 2009 were retrospectively analyzed. The primary endpoint was overall survival (OS), and secondary endpoints were progression-free survival (PFS) and adverse effects according to the type of hysterectomy. Results: A total of 247 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In the present study, factors associated with local recurrence included stage, postmenopausal status, and histological type 2. Previous studies reported that factors related to PFS included age, tumor grade, myometrial invasion, and stage [1012] and those affecting OS included age, tumor grade, stage, and vascular invasion [1, 11, 12, 16]. These results are similar to those of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, factors associated with local recurrence included stage, postmenopausal status, and histological type 2. Previous studies reported that factors related to PFS included age, tumor grade, myometrial invasion, and stage [1012] and those affecting OS included age, tumor grade, stage, and vascular invasion [1, 11, 12, 16]. These results are similar to those of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…A retrospective study conducted in Japan by Morikazu et al on SH and mRH for 247 patients with stage I and stage II endometrial cancer [12] reported the PFS and OS did not significantly differ between the groups. In a randomized controlled trial of extrafascial SH and mRH performed on 520 patients with stage I endometrial cancer, Mauro et al reported no significant difference between the two groups in terms of disease-free survival and OS [10].…”
Section: Discussionmentioning
confidence: 99%
“…The goals of this surgical management are to obtain an optimal cytoreduction and identify parametrial involvement, with the consequent change in clinical staging, prognosis, and need for adjuvancy [4]. It should be noted that radical hysterectomy carries a risk of complications that could delay adjuvancy [5]. Additionally, cervical involvement could be associated with other poor prognostic factors, such as lymphovascular invasion, unfavorable histologies, deep myometrial invasion, and ovarian and lymph node involvement [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the rate of postoperative infection or the volume of blood loss may also increase. In Miyamoto's study, similar results were confirmed [19]. There was a correlation between a longer operation time and more frequent development of severe adverse events, such as blood loss and lymphedema.…”
Section: Discussionmentioning
confidence: 60%